Fpr2 exacerbates Streptococcus suis-induced streptococcal toxic shock-like syndrome via attenuation of neutrophil recruitment - Ni, Chengpei; Gao, Song; Li, Xudong; Zheng, Yuling; Jiang, Hua; Liu, Peng; Lv, Qingyu; Huang, Wenhua; Li, Qian; Ren, Yuhao; Mi, Zhiqiang; Kong, Decong; et al. (Frontiers in Immunology, 2023)
The life-threatening disease streptococcal toxic shock-like syndrome (STSLS), caused by the bacterial pathogen Streptococcus suis (S. suis). Proinflammatory markers, bacterial load, granulocyte recruitment, and neutrophil extracellular traps (NETs) levels were monitored in wild-type (WT) and Fpr2-/- mice suffering from STSLS. LXA4 and AnxA1, anti-inflammatory mediators related to Fpr2, were used to identity a potential role of the Fpr2 in STSLS development. We also elucidated the function of Fpr2 at different infection sites by comparing the STSLS model with the S. suis-meningitis model. Compared with the WT mice, Fpr2-/- mice exhibited a reduced inflammatory response and bacterial load, and increased neutrophil recruitment. Pretreatment with AnxA1 or LXA4 impaired leukocyte recruitment and increased both bacterial load and inflammatory reactions in WT but not Fpr2-/- mice experiencing STSLS. These results indicated that Fpr2 impairs neutrophil recruitment during STSLS, and this impairment is enhanced by AnxA1 or LXA4. By comparing the functions of Fpr2 in different S. suis infection models, inflammation and NETs was found to hinder bacterial clearance in S. suis meningitis, and conversely accelerate bacterial clearance in STSLS. Therefore, interference with neutrophil recruitment could potentially be harnessed to develop new treatments for this infectious disease.